Multi‐country rapid adverse drug event assessment: the Asian Pharmacoepidemiology Network (AsPEN) antipsychotic and acute hyperglycaemia study. (21st May 2013) - Pratt, Nicole; Andersen, Morten; Bergman, Ulf; Choi, Nam‐Kyong; Gerhard, Tobias; Huang, Cecilia; Kimura, Michio; Kimura, Tomomi; Kubota, Kiyoshi; Lai, Edward Chia‐Cheng; Ooba, Nobuhiro; Ösby, Urban; et al.
ABSTRACT Purpose To undertake a multi‐country study to investigate the risk of acute hyperglycaemia with antipsychotic use. Methods Using a distributed network model with a common minimal data set, we performed a prescription sequence symmetry analysis (PSSA) to investigate the risk of acute hyperglycaemia associated with antipsychotic initiation. Incident insulin prescriptions were used as a proxy indicator of acute hyperglycaemia. Participating countries and population datasets included Australia (300, 000 persons), Japan I (300, 000 persons), Japan II (200, 000 persons), Korea (53 million persons) Taiwan (1 million persons), Sweden (9 million persons), USA‐Public (87 million persons) and USA‐Private (47 million persons). Results Olanzapine showed a trend towards increased risk in most databases, with a significant association observed in the USA‐Public database (Adjusted sequence ratio (ASR) = 1.14; 95% Confidence Interval (CI) 1.10–1.17) and Sweden (ASR = 1.53; 95% CI 1.13–2.06). Null or negative associations were observed for haloperidol, quetiapine and risperidone. Conclusion Acute hyperglycaemia appears to be associated with olanzapine use, however, this effect was only observed in two large databases. Despite different patterns of utilization of both antipsychotics and insulin, PSSA analysis results for individual antipsychotic medicines were qualitatively similar across most countries. PSSA, used in conjunction with existing methods, may provide a simple and timely method further supporting multi‐national drug safety monitoring. Copyright © 2013 John Wiley & Sons, Ltd.